Comparison of Endotracheal Reintubation between Nasal High-Frequency Oscillation and Continuous Positive Airway Pressure in Neonates - Thatrimontrichai, Anucha; Sirianansopa, Kantisa; Janjindamai, Waricha; Dissaneevate, Supaporn; Maneenil, Gunlawadee (American Journal of Perinatology, 2020)
Objective This study aimed to compare the endotracheal reintubation between nasal high-frequency oscillation (nHFO) and nasal continuous positive airway pressure (nCPAP) with face mask groups who were followed up for up to 7 days.Study Design We performed a retrospective cohort study of extubated neonates admitted between 2013 and 2017. We used a Cox's proportional hazards model to adjust for significant between-group differences in baseline characteristics.Results One hundred and ninety-nine neonates were on either nHFO or nCPAP after extubation. The median (interquartile range) gestational age and birth weight were 31 (29, 33) weeks and 1,450 (1,065, 1,908) grams, respectively. From the univariate analysis, gestational age, ventilator modes, mean airway pressure, fraction of inspired oxygen, oxygen index, caffeine therapy, and initial continuous positive airway pressure level were significantly different between the nHFO and nCPAP groups. There was no significant difference in the 7-day reintubation rate of neonates on nHFO compared with nCPAP (hazard ratio: 2.39; 95% confidence interval: 0.97–5.84; p = 0.05). By multivariate analysis, there was no statistically significant difference of reintubation rate between nHFO and nCPAP by Cox's proportional hazards model.Conclusion The nHFO mode with face mask is the choice for noninvasive ventilation to prevent reintubation during the week following extubation.
Keywords: airway; extubation; continuous positive airway pressure; high-frequency oscillation; newborn; noninvasive ventilation; reintubation